Level of Satisfaction of Geriatric People about Services Provided by an Old Home at Gajipur, Bangladesh (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: With increased life expectancy and an increased proportion of older people, the demand for old-age homes is increasing. A satisfactory quality of service provision from old age homes can enhance the overall quality of life of an old person. This study aims to assess the level of satisfaction of geriatric people, with the services provided by the Bayaska Punarbasan Kendroy (an old home), situated at Gajipur, Bangladesh.Methods: This descriptive study was designed to evaluate the level of satisfaction of the residents of the Bayaska Punarbasan Kendro about the services provided there. The study was carried out at the Department of Community Medicine, Rajshahi Medical College, Rajshahi over a period of 1 year from January 2019 to December 2019. A total of 200 respondents (residents) were consecutively included in the study based on predefined enrollment criteria. To determine the level of satisfaction of the residents of the Bayaska Punarbasan Kendro about the services provided there, the respondents’ opinion was sought about how well they were satisfied with each of those services. The responses given to each discrete question were scored from 0-4 using Likert Scale, where 0 meant “highly dissatisfied”, and 4 meant “highly satisfied”, with 1 “dissatisfied”, 2 “neither dissatisfied nor satisfied”, and 3 “satisfied” in between them. The scores obtained thus were then summed up to find an integrated score, which ranged from 0-32. The total score was then subdivided into five categories as scores 0-6 (highly dissatisfied), scores 7-12 (dissatisfied), scores13-18 (neutral), scores 19-25 (satisfied), and scores 26-32 (highly satisfied).Result: About two-thirds of the residents of the Bayaska Punarbasan Kendro were Muslim and in their 7th decade of life. More than 55% had already lost their spouses. Fifty percent of the residents came from rural regions. Half of the respondents did not have any income source and the rest half were facing economic hardship. About one-quarter (24.5%) of the respondents were illiterate, nearly two-fifths (37.5%) were primary-level educated and 9% were graduate-level educated. Day labourers comprised almost one-third followed by housewives and service holders. Residents of the old homes were invariably suffering from some sort of physical and mental illnesses concurrently with42% having multiple physical ailments. The major chronic disease was CHD followed by diabetes and osteoarthritis. Nearly half (47%) of the respondents were satisfied with the services provided by the old home, 25.5% were dissatisfied and the rest 27.5% were neither satisfied nor dissatisfied. Probing about the status of living of the old home residents revealed that over one-third (35.5%) had been residing there for < 1 year, 28.5% for 1-3 years, 30% for 3-5years, and only 5.5% for 5 years or more. More than one-third of the respondents had been residing there for < 1 year and only 5% for 5 years or more. Over three-quarters never communicated with their family members since they were admitted to the Bayaska Punarbasan Kendro. However, their children, spouses, or siblings communicated with the moccasionally. They passed their leisure time working (22%), gossiping (29%), watching TV (35.5%), and hangout orreading books (13.5%). Regarding the level of satisfaction, less than half (47%) of the respondents were satisfied with the overall services. The respondents’ level of dissatisfaction was highest with healthcare facilities (37%), followed by accommodation (28%), food service (21%), clothing (17.5%), and leisure time activities (10.5%). The majority (95%) of the respondents was satisfied with the security system and the social media services.Conclusion: The study concluded that the old-home residents time and again miss their family members and are not happy living there. Nearly one-third of the old-home residents are forced to stay there by their family members and half live there for none of their children or close relatives live in the country and one-quarter do not have any residence to live. None of them has any interest to live there. Almost half are satisfied with the services provided by the old home, over one-quarter are dissatisfied and another one-quarter are neither satisfied nor dissatisfied. The respondents’ level of dissatisfaction is mostly with healthcare facilities.Ibrahim Card Med J 2022; 12 (2): 46-52